The intra- and inter-grader reliability of Meibomian gland loss measurement - Kamarul Zaman, Nur Aizzah Hanan; Che Azemin, Mohd Zulfaezal (IIUM Press, International Islamic University Malaysia, 2018)
Previous work employed digital image analysis using a fully-automated computer software to quantify changes in MG, which is meibomian gland loss. However, semi-automated software is more favorable for clinical applications as it allows clinicians to manually delete undesired noise or artifacts. Purpose: To study the intra- and inter-grader reliability of meibomian gland loss (MGL) analysis using a semi-automated computer software. Methodology: This is a retrospective study as participants’ data were readily available from previous study. A total of 192 individual meibography images of meibomian gland (MG) from 48 subjects were loaded into ImageJ software. The MGL areas per total areas were manually traced and reported in percentage. The agreement within- and between-examiners were analyzed using intra-class correlation (ICC) and Bland-Altman plot. Results: ICC results showed only right and left upper eyelid were significantly correlated and showed excellent reliability for both intra- (RE: 0.944) (LE: 0.948) and inter-grader (RE: 0.831) (LE: 0.725) with p-value of less than 0.01. Meanwhile for the lower eyelid, the intra-grader result showed that only right lower eyelid had fair reliability with ICC of 0.525 (p = 0.005). The rest of the results showed poor reliability and the result was not significant. Conclusion: This method of measuring MGL area was only reliable in measuring the upper eyelid for both intra- and inter-grader. The definition of MG, and the interpretation of MGL area should be standardized. It is time consuming and might not be suitable to be used in routine eye examination